2022
DOI: 10.1016/j.cej.2021.132472
|View full text |Cite
|
Sign up to set email alerts
|

A pH-engineering regenerative DNA tetrahedron ECL biosensor for the assay of SARS-CoV-2 RdRp gene based on CRISPR/Cas12a trans-activity

Abstract: In this work, we constructed an exonuclease III cleavage reaction-based isothermal amplification of nucleic acids with CRISPR/Cas12a-mediated pH-induced regenerative Electrochemiluminescence (ECL) biosensor for ultrasensitive and specific detection of SARS-CoV-2 nucleic acids for SARS-CoV-2 diagnosis. The triple-stranded nucleic acid in this biosensor has an extreme dependence on pH, which makes our constructed biosensor reproducible. This is essential for effective large-scale screening of SARS-CoV-2 in areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…As previous literature reported [ 19 , 20 ], the UV–Vis spectrum of the g-C 3 N 4 /Au hybrid has a matching spectral overlap with the ECL emission spectrum of Ru centered at 460 nm, indicating that energy transfer from the g-C 3 N 4 /Au donor to the Ru acceptor can occur. Therefore, in the construction of the present sensor, only the emission peak of the ECL of g-C 3 N 4 (460 nm) needs to be excited, which excites the emission peak of Ru at 620 nm can be obtained using a filter.…”
Section: Resultssupporting
confidence: 74%
“…As previous literature reported [ 19 , 20 ], the UV–Vis spectrum of the g-C 3 N 4 /Au hybrid has a matching spectral overlap with the ECL emission spectrum of Ru centered at 460 nm, indicating that energy transfer from the g-C 3 N 4 /Au donor to the Ru acceptor can occur. Therefore, in the construction of the present sensor, only the emission peak of the ECL of g-C 3 N 4 (460 nm) needs to be excited, which excites the emission peak of Ru at 620 nm can be obtained using a filter.…”
Section: Resultssupporting
confidence: 74%
“…Scheme 1 illustrates the mechanism of the target-triggered cascade signal amplification for electrochemical assay of SARS-CoV-2 RNA. We have selected a 26-nucleotide sequence from the SARS-CoV-2 RdRp gene located in the ORF1ab region as the target [ 15 ], which can distinguish SARS-CoV-2 from other coronaviruses with high specificity [ 30 , 31 ]. The designed hairpin HP1 and HP2, which exist complementary sequences, can maintain independent stable structures separately, because their complementary sequences are blocked in their stems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They reported a linear range of 10 aM–500 aM and a detection limit as low as 12.8 aM. Zhang et al [ 59 ] have reported the identification of the same gene (SARS-CoV-2 RNA-dependent RNA polymerase (RdRp)) using a pH engineered regenerative DNA tetrahedron and CRISPR-Cas12a as the amplification method ( Fig. 3 A).…”
Section: Ecl Biosensors For Viruses Detectionmentioning
confidence: 99%
“…
Fig. 3 A: Schematic of the pH-induced biosensor for the detection of SARS-CoV-2 RdRp gene [ 59 ]. B: Scheme of the ECL DNA biosensor development [ 60 ].
…”
Section: Ecl Biosensors For Viruses Detectionmentioning
confidence: 99%